Hak asasi manusia: Pilar utama kehidupan berbangsa dan bernegara - Jazuli, Achmad Chaidar (Maliki Interdisciplinary Journal, 2026)
Human Rights (HR) are fundamental rights inherent to every individual from birth and serve as a central pillar in national and state life. This study aims to examine the concept and basic principles of human rights, analyze their implementation and enforcement challenges in Indonesia, and formulate strategies to strengthen human rights protection. The research employs a qualitative approach through a literature review by analyzing relevant legal sources and academic references. The findings indicate that although Indonesia has established a strong legal framework for human rights protection, there remains a gap between normative provisions and practical implementation. Various human rights violations, such as discrimination, violence, and legal injustice, continue to occur due to weak law enforcement, low public awareness, and political and cultural factors. Therefore, comprehensive strategies are needed, including strengthening law enforcement, institutional reform, human rights education, and the wise use of technology. Ultimately, strengthening human rights is expected to foster a democratic, just, and dignified society.